Potensi Implementasi Pendekatan Asset Based Community Development (ABCD) dalam Upaya Pemberdayaan Masyarakat di Kampung Wisata Cigadung: Potensi Implementasi Pendekatan Asset Based Community Development (Abcd) Dalam Upaya Pemberdayaan Masyarakat Di Kampung Wisata Cigadung - Rahmawati, Aulia; Peachilia, Ifally Pramesia Putri; Hanifah, Diva Salma; Humaedi, Sahadi (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2024)
Village was identified as a potential tourist destination for implementing this ABCD approachThis article aims to explain the implementation of the Asset-Based Community Development approach in the Cigadung Creative Village. This research uses a qualitative data analysis method, which involves describing and describing the data collected without intending to make general conclusions. The Cigadung Creative Tourism Village was found to have great potential in the aspects of human capital and social capital. Apart from that, this village has adequate physical capital, reflected in infrastructure and easy access, supported by good environmental capital. Financially, the Cigadung Creative Tourism Village also has sufficient resources to support its development. The Asset-Based Community Development (ABCD) approach is described as an alternative strategy for community development, challenging top-down needs-based approaches and aimed at helping underserved communities. Cigadung Creative Tourism.